OPTIMIZATION OF UMKM PRODUCT MARKETING WITH THE SOSTAC METHOD THROUGH A DIGITAL PLATFORM STUDY IN BLITAR CITY - Subandi, Hendi; Nugraha, Adri Putra; Jazuli, A Muhamad; Munir, Misbakhul; Huda, Choirul (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
Micro, Small, and Medium Enterprises in Blitar City continue to encounter challenges in marketing. Globalization and digitalization necessitate that MSMEs compete effectively in the virtual marketplace. This service aims to enhance the literacy of MSME participants in Blitar City regarding the implementation of the SOSTAC approach to enable them to compete globally in marketing. The employed strategy is Participatory Rural Appraisal (PRA) to foster active community engagement among MSME stakeholders, with universities serving as facilitators. It was observed that MSME participants, in general, remain unfamiliar with the Digital Platform. The rise in literacy concerning SOSTAC motivates MSME stakeholders to develop marketing strategies and thoroughly investigate the functionalities of the Digital Platform, hence enhancing the involvement of MSME online retailers in Blitar City.